Gambaran Pelaksanaan Toolbox Meeting dan Penggunaan Alat Pelindung Diri di Proyek Konstruksi Manggarai “Mainline I” Phase II Nindya Citra Kharisma KSO Jakarta Selatan - Ega Selpia Nurhayati; Siti Rukayah (STIKes Persada Husada Indonesia, 2021)
Toolbox Meeting or Safety Talk is an informal meeting that focuses on occupational safety and health topics such as hazards in the workplace and how to work safely. The Safety Talk/Toolbox Meeting is usually short and takes place at the work location before the start of the work or work shift. This study aims to describe the implementation of the ToolBox Meeting and the use of personal protective equipment in the Manggarai